1998
DOI: 10.1128/iai.66.8.3485-3491.1998
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Innate and Adaptive Immunity in Respiratory Mycoplasmosis

Abstract: Current evidence suggests that host defense in respiratory mycoplasmosis is dependent on both innate and humoral immunity. To further delineate the roles of innate and adaptive immunity in antimycoplasmal defenses, we intranasally infected C3H/HeSnJ-scid/scid (C3H-SCID), C3H/HeSnJ (C3H), C57BL/6J-scid/scid (C57-SCID), and C57BL/6N (C57BL) mice with Mycoplasma pulmonis and at 14 and 21 days postinfection performed quantitative cultures of lungs and spleens, quantification of lung lesions, and histopathologic as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
21
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(28 citation statements)
references
References 43 publications
7
21
0
Order By: Relevance
“…This inflammation was cleared from all of these tissues by week 4. This supports the observation that the B6 mouse strain is resistant to the M pulmonis– induced persistent inflammatory response (34, 43, 44). For B6‐ lpr / lpr and B6‐ gld / gld mice, after infection with M pulmonis , there was a persistent interstitial infiltration in the lung, liver, and kidney that was similar to the persistent inflammation in the joints.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This inflammation was cleared from all of these tissues by week 4. This supports the observation that the B6 mouse strain is resistant to the M pulmonis– induced persistent inflammatory response (34, 43, 44). For B6‐ lpr / lpr and B6‐ gld / gld mice, after infection with M pulmonis , there was a persistent interstitial infiltration in the lung, liver, and kidney that was similar to the persistent inflammation in the joints.…”
Section: Discussionsupporting
confidence: 88%
“…To clarify whether the chronic arthritis observed in B6‐ lpr / lpr and B6‐ gld / gld mice was due to a defect in the clearance of M pulmonis from the joints (knee and elbow), we determined the degree of recovery of Mycoplasma in B6‐ +/+ , B6‐ gld / gld , and B6‐ lpr / lpr mice. Since Cartner et al (34) have previously reported that the spleen is susceptible to mycoplasma infection after systemic dissemination, we also determined the rate of recovery of mycoplasma from the spleens of infected mice.…”
Section: Resultsmentioning
confidence: 99%
“…This emphasizes that the immunogenetic background (mouse strain) is important for the development of M. pneumoniaeassociated AHR. A variety of infectious disease models demonstrate variable host genetic susceptibility to disease expression (22,23,(37)(38)(39)(40). In such models, variation in susceptibility has frequently been correlated with differences in the patterns of immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Prevention and control. Mice mount an effective immune response to Mycoplasma pulmonis, as measured by their recovery from mild infection and their resistance to infection after active or passive immunization (Cartner et al, 1998). Antibodies of various classes are produced locally and systemically, but their role in infection is unclear.…”
Section: Bacterial Diseasesmentioning
confidence: 99%